Public Discourses and Politics on Migration: A Precarious Situation and Dismal Outlook? (Zeitschrift für Migrationsforschung, 2021)
Emotions dominating normative frameworks is not new in the making of migration-related policies or in public discourses on migration. However, this matter has entered a different dimension in the age of populism and post-factualism reshuffling the parameters of this issue to a large extent. I will argue in this article that we can find a mixture of developments that consecutively reveals a state of public discourses that is highly precarious and that needs change and counteraction. Instead of retreating into welltrodden policy issues and overtly neglecting the potentiality for a constructive discourse that includes the deliberation on migration realties and migratory processes and its complexities, a vision is needed for new evidencebased, well-informed, yet not technocratic, forms of discourse and a future of reflexive knowledge production.Öffentliche Diskurse und Migrationspolitik: Eine prekäre Situation und ein düsterer Ausblick?Die Prägung politischer und öffentlicher Migrationsdiskurse durch Emotionen und Normativität ist nicht neu. Im Zeitalter von Populismus und Post- Faktizität hat diese Prägung jedoch Dimensionen angenommen, die die Parameter dieses Sachverhalts deutlich verschieben. Ich werde in diesem Beitrag verschiedene Entwicklungen diskutieren, die einen öffentlichen Diskurs kenntlich machen, der als hochgradig prekär bezeichnet werden kann und der Änderungen sowie Gegenmaßnahmen benötigt. Anstatt bekannte und veraltete Politiken zu rekurrieren und einen potenziell konstruktiven Diskurs zu vernachlässigen, braucht es Ideen und Visionen einer evidenzbasierten, jedoch nicht technokratischen, Form eines Migrationsdiskurses und einer zukünftigen reflexiven Wissensproduktion.
Keywords: Migration; öffentlicher Diskurs; Migrationsdiskurs; Migrationspolitik; Politikproduktion; Post-Faktizität; Wissensproduktion